Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Let f(x)=-2x-3 and g(x)=x2+5x



Find f(-4) - g(1)


Sagot :

Answer:

1

Step-by-step explanation:

f(x) = -2x - 3

f(-4) = -2(-4) - 3

=8 - 3

=5

g(x) = x² + 5x

g(1) = 1² + 5(1)

=1 + 5

=6

=f(-4) - g(1)

=5-6

=-1